1978
DOI: 10.1128/aem.35.5.986-987.1978
|View full text |Cite
|
Sign up to set email alerts
|

Uterotropic activity of cis and trans isomers of zearalenone and zearalenol

Abstract: The cis and trans isomers of zearalenone [2,4-dihydroxy-6-(10-hydroxy-6-oxo-1-undecenyl)-benzoic acid yi-lactone] and zearalenol [2,4-dihydroxy-6-(6,10-dihydroxy-1-undecenyl)-benzoic acid ,u-lactone] were tested for uterotropic activity in the white rat. The metabolites were administered through the oral route (per os) and by topical application to the freshly shaven skin on the back. cis-Zearalenone was significantly more active than trans when fed orally to the rats in the diet or when applied topically by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The presence of ZEA in samples of rotted tissue of sugar beets in the field before harvest as well as cis-zearalenone, ZEA, and trans-ot,1-ZOL in sugar beet fibers is important in that all possess estrogenic activity. The trans-ot-ZOL isomer has about three to four times more estrogenic activity than ZEA, whereas the trans-o-ZOL isomer has about the same activity as ZEA (18,31). Mirocha et al (31) demonstrated that cis-zearalenone has a significantly higher estrogenic activity to rats in the feeding and skin application test.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of ZEA in samples of rotted tissue of sugar beets in the field before harvest as well as cis-zearalenone, ZEA, and trans-ot,1-ZOL in sugar beet fibers is important in that all possess estrogenic activity. The trans-ot-ZOL isomer has about three to four times more estrogenic activity than ZEA, whereas the trans-o-ZOL isomer has about the same activity as ZEA (18,31). Mirocha et al (31) demonstrated that cis-zearalenone has a significantly higher estrogenic activity to rats in the feeding and skin application test.…”
Section: Discussionmentioning
confidence: 95%
“…The trans-ot-ZOL isomer has about three to four times more estrogenic activity than ZEA, whereas the trans-o-ZOL isomer has about the same activity as ZEA (18,31). Mirocha et al (31) demonstrated that cis-zearalenone has a significantly higher estrogenic activity to rats in the feeding and skin application test. In contrast, Peters (37) reported that both isomers have about the same uterotrophic activity when administered orally to mice.…”
Section: Discussionmentioning
confidence: 95%
“…ZEA is synthesized by the head-to-tail condensation of acetate units via the acetate-malonyl-coenzyme A (CoA) enzyme system through a polyketide pathway (Steele et al, 1974;Mirocha et al, 1978). The ZEA biosynthetic cluster genes PKS4, PKS13, ZEB1 and ZEB2 encode a reducing polyketide synthase (PKS), a non-reducing PKS, an isoamyl alcohol oxidase and a basic leucine zipper (bZIP) transcription factor (TF) respectively (Kim et al, 2005b;Gaffoor and Trail, 2006;Lysøe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Zearalenone has been associated with hyperestrogenism and other reproductive disorders in swine (8), cattle (9), and poultry (1, 2, 7). Thus far, the effects of zearalenol, a reduction product of zearalenone, have been evaluated only in the laboratory (5,10,13). ox-Zearalenol (5,19) is about three to four times more estrogenic than zearalenone, whereas the estrogenic effect of 1-zearalenol is about the same or slightly less than zearalenone (10).…”
mentioning
confidence: 99%
“…Thus far, the effects of zearalenol, a reduction product of zearalenone, have been evaluated only in the laboratory (5,10,13). ox-Zearalenol (5,19) is about three to four times more estrogenic than zearalenone, whereas the estrogenic effect of 1-zearalenol is about the same or slightly less than zearalenone (10). Palyusik et al (12) demonstrated that Candida tropicalis could convert zearalenone to zearalenol and theorized that a similar microbial conversion might explain cases of hyperestrogenism in which no zearalenone could be detected in the suspect feedstuffs.…”
mentioning
confidence: 99%